Le dialecte natal: analyse de l’opinion des intellectuels et des villageois de Lituanie - Kačiuškienė, Genovaitė (Slavia Centralis, 2020)
Native Dialect: Analysis of the Opinion of Intellectuals and Villagers from LithuaniaIn the article, based on a research questionnaire conducted in the Faculty of Humanities of the University of Adult Education of Šiauliai, we attempt to ascertain, 1) how the city’s environment and social dependence influence the conception of dialect and its usage, 2) how many intellectuals of Šiauliai of a mature age, who moved from their native region several years ago, still speak dialect or even standard Lithuanian and 3) what their attitude is toward different dialects.
Keywords: Lithuanian; dialect; identity; research questionnaire; sociolinguistic analysis